Pedestrian Block From Ceramic-Based Tiles Waster : Properties, Modelling And Optimization Studies - Chan, Chee Kin (2010)
The management of solid waste materials is a problem in many developing countries including Malaysia. With an increase in urbanization and economic development, solid waste management has become an acute problem due to the emergence of more waste material. Ceramic tiles generated from construction sites were usually delivered to landfills for disposal. A critical shortage of natural aggregates for the production of new pedestrian blocks also occurred, and an enormous amount of ceramic tiles produced from deteriorated and construction sites created severe ecological and environmental problems.